Students’ Environmental Care Character through Environmental Education in Elementary School - Ananda, Rizky Mauliddah; Naila, Ishmatun; Martati, Badruli; Nurdianah, Lutfiyan (Universitas Islam Lamongan, 2024)
This study aims to analyze the development of environmental care character among elementary school students through environmental-based education. The research conducted at SD Pacar Keling V Surabaya employs a qualitative descriptive approach involving five fourth-grade students, their parents, and two class teachers as subjects. Data collection methods include observation, interviews, and documentation. Key findings reveal that students actively engage in activities promoting environmental cleanliness and sustainability. These activities include routine clean-up events like “Clean Fridays” and outdoor initiatives like cleaning Kenjeran Beach. Students demonstrate energy conservation habits by turning off lights and electrical devices when not in use. They also understand the importance of waste separation, although the school currently uses a single trash can for all waste types. Furthermore, students participate in composting activities, utilizing used rice washing water as a primary ingredient, underscoring their practical involvement in environmental care. This study highlights the role of school and home environments in fostering students’ environmental awareness, supported by parental involvement and school programs like the Adiwiyata initiative. Overall, this research underscores the effectiveness of integrating environmental education into the curriculum and school Culture, promoting a sustainable and environmentally conscious mindset among young students.